Radical Mastectomy Efficiently Improves Long-Term Clinical Outcomes in Dogs with Malignant Mammary Tumors - Seung-Hyun Kim; Dae Sung Yoo; Chul-Ho Park; Sang-Ho Lee; Ju-Hwan Lee; Taeho Ahn; Bock-Gie Jung; Jun-Gyu Park; Sang-Ik Park; Chun-Sik Bae (Animals)
The incidence of mammary gland tumors in dogs is a significant issue, characterized by notable rates of malignancy, recurrence, and disease burden. However, the lack of comprehensive information and correlated studies has presented challenges in establishing an effective surgical treatment strategy. In this study, a cohort of 95 dogs diagnosed with mammary tumors underwent evaluation using various surgical methods, medications, ovariohysterectomy, and assessments of margin completeness to analyze clinical outcomes. Significant clinical outcomes were observed following radical mastectomy and conservative surgeries, irrespective of TNM stages and histopathological grade of malignancy. Complete excision demonstrated significantly improved survival time and disease-free interval compared to incomplete excision. It is noted that complete surgical excision provides benefits, even in cases where lymphatic invasion is present. However, further investigations are necessary to validate the clinical results and mitigate side effects from radical mastectomy. Despite postoperative complications, several studies continue to advocate for more radical mastectomies due to their favorable risk-benefit ratio. Moreover, advanced inpatient treatments can now effectively manage or mitigate many of these complications. This study emphasizes the critical role of surgical proficiency and postoperative medication in treating malignant mammary tumors in dogs, and it provides insights that may contribute to the development of more effective treatment strategies for this condition.